A Big Five facet analysis of sub-clinical dependent personality disorder (Dutifulness). (December 2018) - Furnham, Adrian
Highlights: Over 6000 adults completed the NEO-PI-R and the Hogan Development Survey (HDS). The Dutiful (Dependent) scale from the HDS was the criterion variable in all analyses. Dutiful people were Neurotic, Agreeable people who are low on Openness. Dutiful people are also Anxious, Compliant, Self-Conscious, Unassertive and Vulnerable. Abstract: This study aimed to examine a Big Five, normal personality trait, "bright side" analysis of a sub-clinical personality disorder: Dependency Personality Disorder. Around 6000 British adults completed the NEO-PI-R which measures the Big Five personality factors at the domain and the facet level. They also completed the Hogan Development Survey (HDS) which has a measure of sub-clinical Dependency Personality Disorder called Dutiful as one of its eleven dysfunctional interpersonal tendencies. Correlation and regression results confirmed many of the associations between the Big Five domains and facets and sub-clinical Dependency. The Dutiful (Dependent) scale from the HDS was the criterion variable in all analyses. The results showed that those high on Dutiful are highly unstable Neurotic, Agreeable people who are low on Openness. They are Anxious, Compliant, Self-Conscious, Unassertive and Vulnerable. It is thus possible to assess subclinical personality disorder "dark-side" traits, like Dutifulness, in terms of normal "bright-side" traits. Limitations of the study are acknowledged.